The gender dimension of globalization in Latin America and the Carribbean: a review of the literature - Thorin, Maria
The ongoing process of economic globalization has strong social implications. Its advocates argue that it brings economic growth, contributes to job creation and to poverty reduction. Its critics claim that it increases inequality between and within countries thereby furthering the marginalization of vulnerable groups in the society. If it is true that the benefits generated by globalization are distributed unevenly among social groups then questions arise as to which group do women belong. In other words, are there reasons to believe that the effects of globalization do not spread evenly among males and females in all countries and particularly in developing countries? Moreover, can we identify a gender bias in the present development model adopted by most Latin American countries or does it have a neutral impact on both sexes? Since women all over the world suffer the consequences of gender-based discrimination threats posed by globalization to further marginalization of women as well as the opportunities and risks for their empowerment must be carefully examined. This survey will examine the state of the art of the research on the impacts of economic globalization on women in Latin America and the Caribbean. It presents a broad conceptual framework under which the literature, encompassing theoretical, empirical and regional studies, is reviewed. On the basis of this review a regional agenda for future research will be proposed. The immediate objective of the survey is to contribute to the generation of knowledge about the gender dimension of economic globalization in Latin America and the Caribbean and therefore to contribute to the efforts of mitigating the negative, and promoting the positive effects of globalization on women. The paper is structured as follows. This opening chapter contains the introduction and some methodological notes. The second chapter covers the review of the literature as such in five sections. The first section discuss the concept of globalization as it appears in the literature. Section 2 question if, why and how globalization is argued to have gender-based discriminatory impacts and elaborates on how women are differently impacted than men in the productive and reproductive spheres of their lives. Section 3 examines the employment-related effects of global integration from different angles. Section 4 is concerned with the impact of public policies on women and section 5 summarizes other gender-related and globalization-related issues. The final chapter draws on all information presented previously to critically evaluate the present state of regional research. It identifies the weaknesses and strengths of the literature reviewed as well as the missing areas. Those considerations are then presented as a regional research agenda. The appendix contains an annotated bibliography of the literature that was used for the survey. Individual studies were classified according both to countries and topics covered. In the appendix other pieces of information can be found: i) a list of relevant Internet resources, ii) a resource list of researchers and institutions in the field of gender and globalization, and iii) a list of suggested additional reading. It is worth mentioning that the survey also includes references to the literature that were not summarized. This refers to studies that did not fulfill the selection criteria, but which were considered to be of conceptual or methodological relevance for research in the area and were used to illustrate a particular point in the text. Other material that could not be summarized due to limitations in time was included in the bibliography as suggestions for additional reading. There are also references in the text to Internet sites where more essay-like material can be found (reference data such as year and page is not possible to provide for in these cases). However these references were not included in the bibliography. Finally, the survey attempted to organize the review of the literature around some themes but not without difficulties due to a substantial conceptual overlap. The issues at hand are very intertwined and it was not an easy task to insert the literature content under clear headings. Therefore, some repetition was unavoidable.